Systematic Analysis of Cyber ​​Security in the Implementation of Microbiology E-Practical: Case Study on Online Learning Platform - Yorasakhi Ananta; Salsabila Dwi Fitri (SYSTEMIC RESEARCH: Systemic and Information Technology Journal, 2025)
Digital transformation in higher education has encouraged the use of e-practicum as a solution to the limitations of physical laboratories, especially in microbiology learning. However, the increasing use of online learning platforms also brings serious challenges in terms of cybersecurity, especially related to student data, virtual experiment recordings, and access to scientific content. This article presents a systemic analysis of cyber risk vulnerabilities and mitigation strategies in the implementation of e-practicum in microbiology based on an online platform. The case study was conducted at one of the state universities in Indonesia, with a qualitative descriptive approach through interviews, system observations, and documentation studies. The results show that weaknesses in user authentication, data encryption, and access rights management are critical points that need to be addressed. Recommendations are presented in the form of a systemic framework to strengthen cybersecurity resilience in digital microbiology learning.